Early–Middle Jurassic paleogeography reconstruction in the Western Qaidam Basin: Insights from sedimentology and detrital zircon geochronology. (August 2020) - Zhao, Xudong; Zhao, Junfeng; Zeng, Xu; Tian, Jixian; Guo, Zeqing; Wang, Chao; Wang, Di; Hu, Chao
Abstract: The Western Qaidam Basin (WQB) is situated at the northeastern margin of the Tibetan Plateau. It is adjacent to the Altyn Tagh Range to the west and is bordered at the south and north by the Eastern Kunlun Range and Southern Qilian Range, respectively. Sporadic Jurassic outcrops are exposed along the Altyn Tagh Range. Although subsurface data have revealed that the Jurassic rocks also developed in the basin interior, little is known about their distribution and depositional characteristics. Hydrocarbon exploration has revealed that the Lower–Middle Jurassic strata are important source rocks and reservoirs in the WQB. However, due to post-depositional uplifting, exhumation or deep burial, the sediments provenance, paleogeography and the basin properties during the Early–Middle Jurassic in the whole WQB remain less understood. In this study, we examine the sedimentary records combined with detrital zircon U–Pb geochronology based on an analysis of post-depositional modification, to reveal the source-to-sink relationship between the WQB and surrounding potential source areas, and to further reconstruct the Early–Middle Jurassic paleogeography of the WQB. During the Early Jurassic, there were a series of small-scale, separated rift basins which were characterized by proximal sedimentation and rapid facies shift in the WQB. Specifically, the Lower Jurassic sediments in the southern WQB mainly originated from the Eastern Kunlun Range with minor supply from the Paleozoic intrusions that might have been exposed in the hinterland of the Qaidam Block; the provenance in the northern WQB was dominated by the uplift area to the west. There was a broader depression basin in the southern WQB. The Eastern Kunlun Range and the ancestral Altyn Mountains, served as the two dominant source areas for the clastic material of the southern WQB during the Middle Jurassic. Integrated analysis on sedimentology and provenance reveals that the southeastern Tarim Basin and the WQB were likely to have been interconnected or adjacent during Middle Jurassic period. We thus infer that no large-scale strike-slip displacement along the Altyn Tagh Fault occurred during that period. Combining regional tectonic settings, we tentatively suggest that the extensional setting following the orogenic movement in the eastern part of the Paleo–Tethys Ocean could have been responsible for the formation of the Early Jurassic rift basins. By the early Middle Jurassic, the Bangonghu–Nujiang Tethys Ocean and the Mongol–Okhotsk Ocean were subducted northward beneath the Qiangtang terrane and Siberian continent, respectively. These led to the presence of an extensional stress field and the formation of a broader depression basin in the southern WQB during the Middle Jurassic. Paleogeography reconstruction results indicate that the northern WQB should have much potential for hydrocarbon exploration. Graphical abstract: Image 1 Highlights: Sediments supplies in the Jurassic were dominated by multiple sources. Several small-scale rift basins developed in the WQB in the Early Jurassic. A unified depression basin developed in the WQB in the Middle Jurassic. No displacement occurred along the Altyn Tagh Fault during the Early-Middle Jurassic. The northern WQB is a favorable area for further hydrocarbon exploration.